Wavelet filters in image compression - Janardhana Bhat (2008)
In this study, we mainly study the concepts of wavelet transformation starting from Fourier Transformation. This is mainly required to understand the basic concepts of wavelet transformation in relation with image compression. The, we analyze the advantages of wavelet transformation with respect to transformations derived from Fourier analysis.